Novel and Future Therapeutic Drugs for Advanced Mycosis Fungoides and Sézary Syndrome - Oka, Tomonori; Miyagaki, Tomomitsu (Frontiers in Medicine, 2019)
Mycosis fungoides (MF) and Sézary syndrome (SS) are the most common subtypes of cutaneous T-cell lymphoma. The majority of MF cases present with only patches and plaques and the lesions are usually limited to the skin. On the other hand, in some cases, patients show skin tumors or erythroderma followed by lymph node involvement and rarely visceral organ involevement. SS is a rare, aggressive cutaneous T-cell lymphoma marked by exfoliative erythroderma, lymphadenopathy, and leukemic blood involvement. Because patients with relapsed or refractory MF/SS display a poor prognosis and the current treatment options are characterized by high rates of relapse, there is unmet need for the efficient treatment. This review provides a discussion of the recent and future promising therapeutic approaches in the management of advanced MF/SS. These include mogamulizumab, brentuximab vedotin, alemtuzumab, immune checkpoint inihibitors, IPH4102 (anti-KIR3DL2 antibody), histone deacetylase inhibitors (vorinostat, romidepsin, panobinostat, belinostat, and resminostat), pralatrexate, forodesine, denileukin diftitox, duvelisib, lenalidomide and everolimus.